Treatment of Legal Liability in Russian Theory of Law - SHAPSUGOV, Damir Y.; RADACHINSKY, Yuri N.; KUROCHKIN, Andrey V. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The article is devoted to the issues of formation of general theory of legal ability. The author makes an attempt to evaluate the prospects of legal liability studies, together with psychological, pedagogical, and philosophical research as a solution of common social issues. The purpose of the research is to determine the conditions of formation of the general theory of legal liability as part of the theory of social responsibility, the scientific search for solutions to problems of implementation and enforcement of legal responsibility in the modern Russian legal system. The methodological basis of the study includes comparative analysis of systemic theories of responsibility in various social sciences and axiomatic method in the formation of the primary statements about the nature of legal liability. Justification of main conclusions is carried out by reference to the enabling legislation of the courts of the Russian Federation. The result of the study was the thesis of the author on the admissibility in law notions of responsibility and new approaches to the determination of the place of legal liability in the legal system in Russia. In particular, this approach enables rethinking the purpose and methods of achieving legal responsibility in the formation of law.